2021
DOI: 10.21511/imfi.18(2).2021.09
|View full text |Cite
|
Sign up to set email alerts
|

Volatility dynamics and the risk-return relationship in South Africa: A GARCH approach

Abstract: This study is aimed at investigating the volatility dynamics and the risk-return relationship in the South African market, analyzing the FTSE/JSE All Share Index returns for an updated sample period of 2009–2019. The study employed several GARCH type models with different probability distributions governing the model’s innovations. Results have revealed strong persistent levels of volatility and a positive risk-return relationship in the South African market. Given the elaborate use of the GARCH approach of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…In order to model and predict the volatility of the South African stock market, researchers have traditionally used various variants of the popular GARCH model. A comprehensive review of this literature is beyond the scope and objective of this paper, but the interested reader can refer to the works of [33,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], and the references cited therein. In terms of the international literature on modeling and predictability of stock market volatility, see [33,[53][54][55][56][57] for detailed reviews.…”
Section: Brief Discussion Of Stock Return Volatility Literature Of So...mentioning
confidence: 99%
“…In order to model and predict the volatility of the South African stock market, researchers have traditionally used various variants of the popular GARCH model. A comprehensive review of this literature is beyond the scope and objective of this paper, but the interested reader can refer to the works of [33,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], and the references cited therein. In terms of the international literature on modeling and predictability of stock market volatility, see [33,[53][54][55][56][57] for detailed reviews.…”
Section: Brief Discussion Of Stock Return Volatility Literature Of So...mentioning
confidence: 99%
“…The leverage effect was evident. A research study by Dwarika et al [28] revealed that the South African market has a high level of volatility persistence.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Realized volatility, as captured by the (log) square root of the sum of squared daily log-returns (following [24]), is considered as an accurate, observable, and unconditional metric of volatility [25], unlike the measures of the same derived from the popular alternative types of GARCH models, that has been primarily used in the South African stock market context to capture volatility (see for example, [26][27][28][29][30][31][32][33][34][35][36], and references cited therein), as well as the stochastic volatility (SV) framework. At this stage, it must be noted, within the GARCH-class of models, volatility analysis in South Africa has been dominated by univariate frameworks, and when multivariate-settings were indeed adopted to capture information of predictors, focus was primarily on domestic variables [37][38][39]. More importantly, we use quantile random forests [40], a flexible datadriven machine learning technique, to derive inferences from our prediction models.…”
Section: Introductionmentioning
confidence: 99%